2014
DOI: 10.4141/cjas2013-016
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Effect of dietary lysine content and sanitation conditions on performance of weaned pigs fed antibiotic-free diets

Abstract: Kahindi, R. K., Htoo, J. K. and Nyachoti, C. M. 2014. Short Communication: Effect of dietary lysine content and sanitation conditions on performance of weaned pigs fed antibiotic-free diets. Can. J. Anim. Sci. 94: 115–118. One hundred and ninety-two piglets (7.2±0.50 kg body weight) were fed corn–wheat–soybean meal based-diets to determine dietary Lys requirement in a 2×4 factorial setting [two sanitation conditions (SC): clean and unclean, and four dietary lysine contents: 0.94, 1.09, 1.25 and 1.43%]. The ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 8 publications
2
12
0
Order By: Relevance
“…2, piglets raised under unclean sanitary conditions had reduced growth performance compared with the values reported by other studies (335 g, NRC, 2012 ; 500 g, Zhang and Kim, 2014 ). This suggests that the sanitation model of immune challenge was effective, which is consistent with the findings of others ( Lee et al., 2005 , Le Floc’h et al., 2006 , Kahindi et al., 2014a ) that showed decreased growth performance when piglets subjected to poor sanitary conditions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…2, piglets raised under unclean sanitary conditions had reduced growth performance compared with the values reported by other studies (335 g, NRC, 2012 ; 500 g, Zhang and Kim, 2014 ). This suggests that the sanitation model of immune challenge was effective, which is consistent with the findings of others ( Lee et al., 2005 , Le Floc’h et al., 2006 , Kahindi et al., 2014a ) that showed decreased growth performance when piglets subjected to poor sanitary conditions.…”
Section: Discussionsupporting
confidence: 91%
“…Weaned pigs reared under unclean sanitary conditions was used as a model to provoke a low-grade inflammatory response ( Le Floc’h et al., 2009 , Kahindi et al., 2014a ) and those pigs had reduced growth performance ( Kahindi et al., 2014a ) and activated immune system ( Williams et al., 1997 ) that would interfere with growth because of competition between protein deposition in structural tissues and immune function ( Le Floc'h et al., 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a 21 d experiment, Kahindi (2014) reported that the ADG and G:F were lower for pigs raised under unclean conditions compared with their clean counterparts during d 0 to 14 but the effect on ADG disappeared during d 15 to 21 which suggested that the ability of piglets to deal with an immunological stress improved with age and that they were able to adapt to their environment with time. However, the overall ADG was still lower for pigs raised under unclean conditions compared with those raised under clean conditions indicating that piglets were unable to fully overcome the effects of being subjected to unclean housing conditions ( Kahindi, 2014 ; Kahindi et al, 2014 ). In a meta-analysis by Pastorelli et al (2012) , it was concluded that sanitary challenges negatively affect feed intake and growth, leading to a negative impact on animal well-being and economic losses.…”
Section: Sanitation Challenge Modelmentioning
confidence: 99%
“…Indeed, piglets raised under unclean (UCL) sanitary conditions had reduced growth performance (Kahindi et al 2014a) and an activated immune system , which also induced an inflammatory response (Le Floc'h et al 2006). However, because of its involvement in the immune response, this level of Trp might not be adequate for pigs raised in commercial production conditions, whereby incidences of clinical and subclinical infections are high, especially during the immediate post-weaning period.…”
Section: Introductionmentioning
confidence: 99%